Association between intensity or accumulating pattern of physical activity and executive function in community-dwelling older adults: A cross-sectional study with compositional data analysis - Hyodo, Kazuki; Kitano, Naruki; Ueno, Aiko; Yamaguchi, Daisuke; Watanabe, Yuya; Noda, Takayuki; Nishida, Sumiyo; Kai, Yuko; Arao, Takashi (Frontiers in Human Neuroscience, 2023)
Objective: Previous studies have suggested a positive association between physical activity (PA) and executive function in older adults. However, they did not adequately consider the compositional nature of daily time use and accumulated PA patterns. Therefore, this study aimed to examine the association between intensity or accumulated PA patterns and executive functions (inhibitory control, working memory, and cognitive flexibility) in community-dwelling older adults, considering the interaction of daily time spent in PA, sedentary behavior (SB), and sleep. Method: This cross-sectional study used baseline data from a randomized controlled trial on the effect of exercise on cognitive function conducted between 2021 and 2022. Data from 76 community-dwelling older adults were used in the analysis. The time spent in PA and SB was assessed using an accelerometer, and sleep duration was self-reported. The Stroop task (inhibitory control), N-back task (working memory), and task-switching task (cognitive flexibility) were conducted to evaluate the subcomponents of executive function. Considering various potential confounders, compositional multiple linear regression analysis and compositional isotemporal substitution were performed to examine the association of PA with executive function and to estimate predicted changes in executive function in response to the hypothetical time-reallocation of movement behaviors, respectively. Results: A longer time spent in light-intensity PA (LPA), relative to remaining behaviors, was associated with better Stroop task performance. Moreover, this association was stronger in LPA lasting longer than 10 minutes than in sporadic LPA. Additionally, theoretical 30 minutes/day time- reallocation from SB or sleep to LPA was associated with better Stroop task performance (corresponding to approximately a 5–10% increase). On the other hand, no significant associations of time spent in moderate- to vigorous-intensity PA with any subcomponents of executive function were observed. Conclusion: LPA was positively associated with inhibitory control, and this association was stronger in bouts of LPA than in sporadic LPA. Moreover, reducing the time spent in SB or sleep and increasing the time spent in LPA, especially long-bout LPA, could be important measures for managing inhibitory control in late life. Future large longitudinal and intervention studies are needed to confirm these associations and reveal the causality and underlying mechanisms.